If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 18 = 116 + -6x Reorder the terms: 18 + 6x = 116 + -6x Solving 18 + 6x = 116 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 18 + 6x + 6x = 116 + -6x + 6x Combine like terms: 6x + 6x = 12x 18 + 12x = 116 + -6x + 6x Combine like terms: -6x + 6x = 0 18 + 12x = 116 + 0 18 + 12x = 116 Add '-18' to each side of the equation. 18 + -18 + 12x = 116 + -18 Combine like terms: 18 + -18 = 0 0 + 12x = 116 + -18 12x = 116 + -18 Combine like terms: 116 + -18 = 98 12x = 98 Divide each side by '12'. x = 8.166666667 Simplifying x = 8.166666667
| (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 | | x^2+4x-1=9x-5 | | 6x+30=13-33 | | x^2+8x-2=7 | | x^2-(a+2b)x+b^2+ab=0 | | 24a=36 | | 12-x=30-4x | | 3x+4=5x-16 | | x^2+32x-196=0 | | x-17=6x+8 | | 9x-5=x+19 | | 9x+6=6x+10 | | 7x-20=04-3x | | 7(2x-5)=42 | | 21-7x=10+4x | | x+2=-3x+30 | | (5x-3)*2+(2x+1)*2=34 | | .4x=-5.3 | | 2x+12=4x+2 | | 10-8=30-15x | | 5x+4y+5z-2x+2z-6y= | | 6x+36=8x+20 | | (x+1)*(2x-6)=0 | | 285-4x=41x+20 | | -15+x=x+18 | | 10-7x=170-35x | | 149-7x=20x+20 | | a-6=-21 | | x^2-2x+13=10x-7 |